2015
DOI: 10.18343/jipi.20.3.171
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnobotany Knowledge of Manggarai Tribe and the Implication Utilization of Forest Plants in The Mountains of Ruteng

Abstract: ABSTRAK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…The second largest category is plants used for foods and beverages. This is consistent with the findings of the ethnobotanical survey of Iswandono (2015) in the Ruteng forest of Flores. Iswandono found that the largest group of useful forest plants consisted of medicinal plants, followed by plants used for food.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The second largest category is plants used for foods and beverages. This is consistent with the findings of the ethnobotanical survey of Iswandono (2015) in the Ruteng forest of Flores. Iswandono found that the largest group of useful forest plants consisted of medicinal plants, followed by plants used for food.…”
Section: Resultssupporting
confidence: 92%
“…Other kinds of forest plants are used for household needs (Table 1). Iswandono (2015) reported that most tribal communities in Flores have knowledge about medicinal plants from the forests, while indigenous medical practitioners are often considered to have magical power. Medicinal plant use from the forest satisfies a special need, because the people have a belief that forest plants are more beneficial to health than garden plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local comunities living around the forest have interacted and know the sustainable use of forest plants (Pei et al 2009). Ethnobotanical knowledge of local community has an important role in managing and conserving of the forest properly (Iswandono et al 2015). This knowledge is further used as a role model for development of community wisdom in the future.…”
Section: Knowledge Of Pelawan Padang Based On the Agementioning
confidence: 99%
“…Various protective efforts based on legal enforcement instruments are unable to achieve significant outcomes, because illegal cutting and logging within the forest actually continues despite these measures. Iswandono et al (2015) in his research among the Manggarai people gained knowledge of community efforts aimed at minimizing the impact of using trees as building materials. The Manggarai perform traditional ceremonies when felling large trees from the forests to build a house.…”
Section: High Risk (Low Potential For Sustainability)mentioning
confidence: 99%